Implementation of Digital Leaderships on Pertamina Hulu Energy in Aceh - Matriadi, Faisal; Ikramuddin, Ikramuddin; Adamy, Marbawi; Chalirafi, Chalirafi (Malikussaleh University, Aceh, Indonesia, 2021)
This study examines the effect of Digital Leadership and workplace spirituality on the performance of Pertamina Hulu energy employees with job satisfaction as an intervening variable. A population of 136 employees were all used as respondents or using a saturated sample model. The analytical tool used is the SEM (structural equation modeling) method using Amos. The results showed that each variable, both digital leaderships and workplace spirituality, had a positive and significant effect on job satisfaction and employee performance at Pertamina Hulu Energy. Furthermore, the job satisfaction variable mediates workplace spirituality with the performance variable partially mediating and the job satisfaction variable mediating digital leaderships with the performance variable. also partially mediation.